Dapithapon - Uy, Edsel Brady Lim
The film is set in present time, the Philippines. The earth's rotation is slowing down due to the abuse of nature done by humanity, extending days and nights. Nardo, a biotechnologist, and his son Victor are tasked to research a way in which genetically modified corn can be propagated in perpetual sunlight in anticipation of year's length of daytime. This research is to provide a long term solution for the resource of food which is becoming increasingly scarce. Some implications of the ceasing of the Earth's rotation include year-long days and nights, global catastrophe and ultimately, the demise of society. Miguel, a representative of the company funding this research, pressures them as he cuts short the amount of time left for them to research.